Central fatigue aetiology in prolonged trail running races. Issue 3 (18th January 2021) - Espeit, Loic; Brownstein, Callum G; Royer, Nicolas; Besson, Thibault; Martin, Vincent; Millet, Guillaume Y; Lapole, Thomas
Abstract : New Findings: What is the central question of this study? Are spinal and/or supraspinal perturbations implicated in central fatigue induced in the plantar flexor muscles following prolonged trail running races? What is the main finding and its importance? The study confirmed the presence of central fatigue following various trail running distances from 40 to 170 km. The reduction in the V‐wave in conjunction with the lack of change in the H‐reflex suggests that a major component of this central fatigue may arise from supraspinal mechanisms in the plantar flexor muscles. Abstract: Trail running races are known to induce considerable impairments in neuromuscular function of which central mechanisms are a substantial component. However, the loci of this central fatigue (i.e. supraspinal and/or spinal) is not well identified. The aim of this study was to better understand central fatigue aetiology induced in the plantar flexor muscles by various trail running distances from 40 to 170 km. Eighteen runners participated in the study and neuromuscular function of their plantar flexors was tested before (PRE) and after (POST) various races during the Ultra‐Trail du Mont Blanc. Neuromuscular function was evaluated with voluntary and evoked contractions using electrical tibial nerve stimulation. H‐reflex and V‐wave responses were also measured during submaximal and maximal voluntary contraction, respectively. Reductions in maximal voluntary contraction torque (−29%; P < 0.001) and voluntary activation level (−12%; P < 0.001) were observed after trail running races. The V‐wave was reduced in soleus (−35%; P = 0.003) and gastrocnemius medialis (−28%; P = 0.031), with no changes for the H‐reflex in soleus ( P = 0.577). The present study confirmed the presence of central fatigue following trail running exercise. The reduction in the V‐wave in conjunction with the lack of change in the H‐reflex suggests that a major component of this central fatigue may arise from supraspinal mechanisms. Abstract :